2023
DOI: 10.1101/2023.03.08.531698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone variants shape chromatin states in Arabidopsis

Abstract: How different intrinsic sequence variation or regulatory modifications of histones regulate nucleosome interactions with transcription remain unclear. To clarify this question, we examine how histone variants and histone modifications assemble in the Arabidopsis thaliana genome, and show that a limited number of chromatin states divide euchromatin and heterochromatin into biologically significant subdomains. We find that histone variants are as significant as histone modifications in determining the compositio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 97 publications
1
17
0
Order By: Relevance
“…Consistent with ours (Fang et al 2020) and other reports (Qi et al 2022) among the top-hits we also found FLD (Figure 2A). Interestingly, one of the highest hits was the histone H2A.W.7, a variant exclusively found on constitutive heterochromatin (Lorković et al 2017, Jamge et al 2023, suggesting a generic role for APRF1 in co-transcriptional gene repression. Given this robust APRF1-LD interaction, we considered if LD could be the homolog of one of the yeast Swd2 partners in the CPF or the APT phosphatase modules (Casanal et al 2017, Lidschreiber et al 2018).…”
Section: Ref2/pnutsmentioning
confidence: 99%
“…Consistent with ours (Fang et al 2020) and other reports (Qi et al 2022) among the top-hits we also found FLD (Figure 2A). Interestingly, one of the highest hits was the histone H2A.W.7, a variant exclusively found on constitutive heterochromatin (Lorković et al 2017, Jamge et al 2023, suggesting a generic role for APRF1 in co-transcriptional gene repression. Given this robust APRF1-LD interaction, we considered if LD could be the homolog of one of the yeast Swd2 partners in the CPF or the APT phosphatase modules (Casanal et al 2017, Lidschreiber et al 2018).…”
Section: Ref2/pnutsmentioning
confidence: 99%
“…1, C and D). To further substantiate this perspective, we examined the accumulation of different histone marks and histone variants at Paf1C target genes (Jamge et al, 2023). Paf1C target genes were enriched in histone marks associated with active gene transcription, such as H3K4me3 and H3K36me3, while being depleted of the Polycomb -based H3K27me3 mark (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-seq reads of H3, H3K4me3, H3K36me3, H3K27me3, and H2A.Z (GSE231408; samples GSM7075958, GSM7075959, GSM7075961, GSM7075962, GSM7075963, GSM7075964, GSM7075985, GSM7075986 and GSM7075990) (Jamge et al, 2023) were analysed as described in ChIP-seq analysis. MNase-seq reads of wild type Col-0 (GSE205110; samples GSM6205325 and GSM6205326) (Diego-Martín et al, 2022) were downloaded, processed and aligned as described in ChIP-seq analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, those representing RNAP IV subunits or components of the microtubule assembly machinery typically have only one DEG in most species examined (Figure 3 and Figure S4). Importantly, histone variants are emerging as modulators of chromatin architecture (Borg et al, 2021;Bhagyshree et al, 2023). The histone proteins that we identified in this conserved cluster of enriched OGs are therefore strong candidates for determining the specific chromatin state of the endosperm.…”
Section: The Conserved Transcriptional Network Of the Angiosperm Seed...mentioning
confidence: 86%
“…Histone variants contribute to the definition of chromatin states and gene expression patterns. By modifying chromatin structure, they regulate the accessibility of DNA, influence gene expression, contribute to epigenetic inheritance, and participate in plant responses to environmental cues and developmental processes (Borg et al, 2021;Bhagyshree et al, 2023). Interestingly, histone variants were exclusively present in the shared protein network and not in any of the private sets of proteins specific to particular plant clades.…”
Section: Conserved Transcriptional Features Of the Angiosperm Endospermmentioning
confidence: 99%